Televising Rural Muslim Culture: Hybrid Muslim Identities on TV Series Upside-Down World - Hakim, Lukman (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2017)
this article aims to contribute to the current understanding of how the religious-based TV drama Upside-Down World (Dunia Terbalik) depicts the identity of rural-based Muslim society in the contemporary Indonesia. Utilizing a formal method of film criticism, it reveals that the soap opera Dunia Terbalik simulates 'a hybrid new Santri identity' as well as it blurs the existing identities like Geertz' classification of santri. Further, the reculturization occurs within TV drama narrative, through which hybrid new Santri identity constructed, is likely intended to convey the notion that Indonesian Islam (Santri) should be globalized, and the global should be Santrinisized